Three-dimensional oil spill transport and dispersion at sea by an event of blowout (2014)
The simulated droplet trajectories of the 3-D model at the Caribbean platform showed that droplets with a diameter of 50 µm formed a distinct subsurface plume, which was transported horizontally and could remain below the surface. This plume could have a very restricted area of impact because the dispersion is only controlled by the ocean currents which, at 1000 m depth, have a low intensity and are quite turbulent. In this case, the formed plume stayed trapped at 1000 m depth, not posing a risk to the Caribbean Coast. In contrast, droplets with diameters of 250 µm, 1 and 10 mm rose rapidly to the surface, even with different velocities (6, 10, 20 ms-1)..